(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The furniture industry in Karyamukti Village produces significant wood waste that is generally underutilized, while the demand for educational play tools continues to grow in early childhood and elementary education. This study aims to empower local furniture craftsmen by improving their skills in converting production waste into educational play tools and enhancing their digital marketing capabilities. A participatory community empowerment approach was applied through observation, problem identification, hands-on training in educational play tool production, and digital marketing assistance using online marketplaces such as TikTok Shop and Shopee. The program successfully produced five educational play tool prototypes: connecting word, intelligency stick, alphabet puzzle, shape puzzle, and domino number puzzle. Participants showed increased knowledge and practical skills in utilizing wood waste, along with improved ability to market products digitally. A positive shift in perception was also observed, with participants recognizing furniture waste as a resource with economic value. Integrating production training and digital marketing effectively enhances community capacity, increases the economic value of furniture waste, and supports sustainable local development. Continuous mentoring is recommended to ensure product quality and expand market access.